Exploring the factors influencing urban farmers’ perception and attitude toward the use of excreta-based organic fertilizers in Arba Minch City, Ethiopia - Ejigu, Abrham Kassa; Yeshitela, Kumelachew (Frontiers in Sustainable Food Systems, 2024)
This study assesses the factors influencing urban farmers’ intentions to adopt excreta-based organic fertilizers in Arba Minch City, Ethiopia, to address the pressing global resource use challenge, particularly the linear system of organic nutrient use and the practice of closing the nutrient loop. To do this, the study applies the Combined Model of Theory of Planned Behavior and Technology Acceptance Model (C-TPB-TAM) to examine the links between attitude, subjective norm, perceived behavioral control, perceived usefulness, perceived ease of use, and farmers’ intentions. Surveys that were given to a sample of urban farmers in Arba Minch City were used to get the data. The results shed light on the factors that influence farmers’ decisions to use organic fertilizers and offer useful information for resolving the problem of resource use in the context of urban agriculture. The findings specifically show how attitudes, perceived behavioral control, perceived usefulness, and perceived ease of use significantly affect farmers’ intentions. However, it was discovered that the subjective norm did not significantly affect the farmer’s intention. These results highlight how critical it is to address farmers’ attitudes, perceived behavioral control, perceived usefulness, and perceived ease of use to encourage the adoption of sustainable farming methods and close the nutrient loop. Farmers can help mitigate the negative environmental effects of the linear nutrient system and speed up the transition to a more resource- and sustainably efficient agriculture system by implementing organic fertilizers. This study not only adds to the body of knowledge but also has applications for practitioners and policymakers who want to encourage the use of organic fertilizers. To better understand the adoption of organic fertilizer in various locations and nations, future research projects should think about extending the geographical reach and examining real adoption behavior. We can encourage sustainable agricultural practices and work toward a more resource-oriented and resilient future by building on these lessons.